Comparative Analysis of the Changes of Socioeconomic Risks Caused by the COVID-19 pandemic in Ukraine and the EU Countries - Novikova, Olga; Khandii, Olena; Shamileva, Larisa (European Journal of Sustainable Development, 2021)
The unwillingness of the health care system of different countries to counteract the spread of the COVID-19 virus in 2020 caused the introduction of quarantine restrictions by many countries, which had both positive and negative socioeconomic consequences. The economic consequences include the decrease in production and income of enterprises of almost all types of economic activity, increase in the number of unprofitable enterprises, closure and temporary suspension of small and medium-sized businesses, decline in real GDP. The economic consequences have led to the increase in intensity and manifestation of negative social consequences, including the increase in unemployment and social insecurity, scale and level of citizen poverty, decline in incomes and loss of working time. Influenced by the social and economic negative factors hindering sustainable development, caused by the COVID-19 pandemic, socioeconomic risks in the social and labor sphere have intensified. The article suggests the methodological support for assessing the change of socioeconomic risks in the system of social and labor relations in Ukraine and the EU countries using quantitative assessment methods. The comparison of risks in the social and labor sphere of different countries allows to choose the prioritized directions of influence and effective tools to control and counteract the manifestation of risks, taking into account the experience of other countries.